Exploring job search and the causes of endogenous unemployment: evidence from Duncan Village, South Africa - Duff, Patrick Alexander (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2009)
Despite high rates of unemployment in South Africa, there is little consensus about its origins and solutions to the problem. Job search (how and when people search for work)is one aspect of the unemployment problem. Job search is shown to be a complex process strongly linked to the endogenous structure of the labour market. The flaws in traditional methods (theoretical and measurement) highlight this. Using data from a tailor-made survey in Duncan Village (a peri-urban area in Buffalo City, South Africa) the research examines factors that influence the effectiveness of job search. The results show that mode of search (how people look for work) is used as a signal by employers. Degrees of success are stratified amongst searchers using either 'word of mouth', place-to-place or formal modes of search. The thesis provides a method-test to reveal a complex body of evidence that has yet to be fully explored by practitioners in this field.
Keywords: Unemployment; Unemployment -- Social aspects -- South Africa -- East London -- Duncan Village; Job hunting -- South Africa -- East London -- Duncan Village; Labor market -- South Africa